PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATEMATIKA BERKONSEP ISLAM PADA MATERI GARIS DAN SUDUT - Miftah Qurrohman Muafi'i; Pika Merliza (LPPM Universitas Bina Bangsa, 2022)
This study aims to develop Islamic-concept mathematical worksheets on line and angle material. This type of research is R&D with a 4D model. To determine the feasibility of the Islamic-concept mathematical worksheets, validity tests and practical tests were carried out. The product validity test was carried out by two experts, namely material experts and media experts. While the practical test was obtained from the responses of educators and students of class VII SMP Muhammadiyah 1 Sekampung Udik. The results of the assessment from material experts reached 79% on the appropriate criteria. Meanwhile, for media experts, the assessment obtained reached 100% on the very feasible criteria. For the results of the practical test through the responses of educators and students who have given a positive response to the Islamic concept worksheet for mathematics on line and angle material, the results of the teacher's response reached 86.66% on the very feasible criteria and on the student response the results obtained 79.70% with proper criteria. For this reason, the results of the development of Islamic-concept mathematical worksheets on line and angle material are declared feasible from the results of product validity and practicality tests